Center of mass direction and speed during a 45-degree change of direction task performed with maximal effort - Yamashita, Daichi; Inaba, Yuki; Asakura, Masaki; Ito, Yoshihiko (Frontiers in Sports and Active Living, 2025)
Changes in whole-body center of mass (COM) direction and speed over multiple steps during a maximal effort change of direction (COD) task have not been fully examined. This study aimed to (1) quantify COM direction and speed changes across three steps —approach (APP), execution (EXE), and following (FOL)—during a 45° COD task, and (2) compare force production between EXE and FOL. Ten male American football players performed straight running (RUN) and sidestep cutting to a 45° COD (COD45) tasks. In RUN, participants sprinted 15 yards (13.73 m) at maximal speed. In COD45, they sprinted 10 yards (9.15 m), executed a 45° cut, and completed an additional 5-yard (4.58 m) sprint. COM speed and direction were analyzed across four flight phases in COD45 (FLIGHT-2, FLIGHT-1, FLIGHT + 1, FLIGHT + 2) and three in RUN (FLIGHT-2, FLIGHT-1, FLIGHT + 1). Horizontal ground reaction impulses (GRIs) during EXE in RUN and EXE and FOL steps in COD45 were analyzed in a local coordinate system aligned with the COM velocity vector. Although COM speed remained unchanged during EXE (between FLIGHT-1 and FLIGHT + 1; p = .053), this step produced a greater medial GRI than FOL (p < .001); however, the direction change during this step was only 15.30°, one-third of the required 45°. APP and FOL contributed 9.70° and 9.05°, respectively, to the direction change while simultaneously increasing COM speed by 0.23 m/s and 0.13 m/s, respectively. Therefore, completing a maximal effort 45° COD requires multi-step role sharing, incorporating both directional changes and acceleration.